2012
DOI: 10.1097/pgp.0b013e31823bb24d
|View full text |Cite
|
Sign up to set email alerts
|

HER2/neu as a Potential Target for Immunotherapy in Gynecologic Carcinosarcomas

Abstract: Carcinosarcomas of the female genital tract are rare tumors with aggressive clinical behavior. Trastuzumab, a humanized monoclonal antibody, acts by binding to HER2/neu extracellular domain and exhibits therapeutic efficacy in HER2/neu over-expressing cancers. Two uterine carcinosarcomas (UMMT-ARK-1, UMMT-ARK-2) and two ovarian carcinosarcomas (OMMT-ARK-1, OMMT-ARK-2) were established as primary tumor cell lines in vitro and evaluated for HER2/neu expression by immunohistochemistry (IHC), fluorescent-in-situ-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…T-DM1, a combination of traztuzumab (anti-HER2/ neu) and mertansine (microtubule polymerization inhibitor) was recently demonstrated by Nicoletti et al [51] to be highly effective at targeting and killing HER2/neu OCS in a mouse model. Guzzo et al [52] reported HER2/neu gene and protein expression in primary carcinosarcoma cell lines and demonstrated trastuzumab-mediated antibody-dependent cellular cytotoxicity against uterine and ovarian carcinosarcomas in vitro.…”
Section: Targeted Therapymentioning
confidence: 97%
“…T-DM1, a combination of traztuzumab (anti-HER2/ neu) and mertansine (microtubule polymerization inhibitor) was recently demonstrated by Nicoletti et al [51] to be highly effective at targeting and killing HER2/neu OCS in a mouse model. Guzzo et al [52] reported HER2/neu gene and protein expression in primary carcinosarcoma cell lines and demonstrated trastuzumab-mediated antibody-dependent cellular cytotoxicity against uterine and ovarian carcinosarcomas in vitro.…”
Section: Targeted Therapymentioning
confidence: 97%
“…Carcinosarcomas can arise in the ovary, cervix or uterus. Previously published data from the SEER database suggests that age adjusted rate of carcinosarcoma development in the uterus is 0.6/100,000 and in the ovary 0.19/100,000 (4). Despite aggressive surgical and adjuvant therapy, 5 year survival rates for uterine carcinosarcoma are approximately 60% for early (stage I/II) disease and 9–22% for more advanced disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…These genetic landscape results are consistent with previous clinical/pathological studies showing that the epithelial component of the carcinosarcoma drives the growth and proliferation of these rare and biologically aggressive gynecologic cancers. Because of the reported overexpression and/or gene amplification of HER2 in over one third of uterine serous carcinoma (12, 13) which represents the high grade epithelial component of a large number of gynecologic CS (10), HER2 may represent an attractive target for anticancer therapy (4). …”
Section: Introductionmentioning
confidence: 99%
“…Carcinosarcomas can arise in the ovary, cervix or uterus. Previously published data from the SEER data base suggests that age adjusted rate of carcinosarcoma development in the uterus is 0.6/100,000 and in the ovary 0.19/100,000 [2]. Despite aggressive surgical and adjuvant therapy 5 year survival rates for uterine carcinosarcoma are approximately 60% for early (stage I/II) disease and 9–22% for more advanced disease [3].…”
Section: Introductionmentioning
confidence: 99%